A fast computational algorithm to evaluate large transmit-arrays - Naseri, P. (2018)
Transmit-arrays (TAs) have become popular solutions for point-to-point communications due to their lowprofile and high-efficiency. However, simulation of these large and detailed structures demands a great amount of memory and time. Here, we propose a fast algorithm to estimate the performance of a beam-steering TA to accelerate its design optimization process. The results and the required resources of the algorithm are compared with the ones of Ansys HFSS. It is shown that this algorithm can fairly evaluate the key factors of the performance of a TA within couple of minutes with memory resource of only 1 GB.